Les enseignants de la formation professionnelle : leur travail, leur réalité - Otilia Holgado (Activités)
This paper attempts to provide an exploratory overview of the daily work of eight teachers from secondary vocational education in Quebec. Six skilled trades are involved: surveying, cooking, landscape maintenance, secretarial work, trucking and driving construction machinery. The study was carried out using a work analysis approach based on open-ended interviews. It aimed to access the representations of participating teachers in order to give an account of how they see their own profession, the tasks of which it is composed and the responsibilities that are theirs, as along with the working conditions, the difficulties they encounter and the means they deploy to deal with the latter on a daily basis. The results show the sharing between prescribed tasks and those voluntarily undertaken by teachers, with the aim of promoting student learning and ensuring the proper functioning of their training centre. We note that this leads to a work overload, the completion of which extends into personal time, leading to a blurred line between professional and private life.